1999
DOI: 10.1038/sj.bmt.1701584
|View full text |Cite
|
Sign up to set email alerts
|

Busulphan level and early mortality in thalassaemia patients after BMT

Abstract: Summary:The aim of the study was to correlate busulphan (BU) levels of thalassaemia patients with outcome of allogeneic transplant. BU levels were measured by gas chromatography mass fragmentography. All patients received a standardised dose of BU 16 mg/kg, and cyclophosphamide 150 or 200 mg/kg. For area-under-thecurve analysis (AUC), blood samples were obtained at 0, 1, 2, 3, 4 and 6 h after the first and fifth dose for all patients, and additional levels were measured after ninth and/or 13th dose in most pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The incidence of hepatic VOD in our study was lower (1.4%) compared with the reported incidence of VOD in children with thalassemia and treated with oral Bu, which varied between 4.5% and 45%. [4][5][6] It has been suggested that dosing Bu close to the dose of Cy may increase hepatotoxicity that occurred more frequently with shorter intervals (7-15 hours) compared with longer intervals (24-48 hours) between the last dose of Bu and the first dose of Cy. 41 In the present study, the interval between the last dose of Bu and the first dose of Cy was 14 hours in 42%, and it was 38 hours in the remaining 58% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of hepatic VOD in our study was lower (1.4%) compared with the reported incidence of VOD in children with thalassemia and treated with oral Bu, which varied between 4.5% and 45%. [4][5][6] It has been suggested that dosing Bu close to the dose of Cy may increase hepatotoxicity that occurred more frequently with shorter intervals (7-15 hours) compared with longer intervals (24-48 hours) between the last dose of Bu and the first dose of Cy. 41 In the present study, the interval between the last dose of Bu and the first dose of Cy was 14 hours in 42%, and it was 38 hours in the remaining 58% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] High-dose busulfan (Bu) combined with cyclophosphamide (Cy) is the preferred preparatory regimen for patients with thalassemia and is a valid alternative to regimens that include total body irradiation. Although the BuCy regimen has been extensively used in patients with thalassemia few data are available on relationship of Bu pharmacokinetics (PK) to transplantation outcome with controversial results: one study found no effect of oral Bu exposure to transplantation outcome, 4 whereas in 2 other studies a relationship between oral Bu PK and rejection, hepatic veno-occlusive disease (VOD), 5 or mortality 6 was observed. These discrepancies might be the result of the unreliability of oral Bu pharmacokinetic assessment because of erratic intestinal absorption and possible dose loss with emesis.…”
Section: Introductionmentioning
confidence: 96%
“…14 In our previous study, busulphan levels (area under curve) greater than 908 mol × min/l were associated with higher mortality. 15 The occurrence of VOD is related to number of transfusions and age. Thus, older patients are at risk of severe VOD and other treatmentrelated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with thalassemia major undergoing BMT are particularly prone to developing HVOD and the incidence can be as high as 30% to 40% 18,19 in those with significant pre-existing hepatic damage. The aim of the present study was to assess whether the polymorphisms of the GST genes are associated with the risk of developing HVOD in this group of patients.…”
Section: Introductionmentioning
confidence: 99%